Animating the Real: Illusions, Musicality and the Live Dancing Body - Read, Jo (The International Journal of Screendance, 2020)
Animation film frequently uses dance and choreography as part of explicit scenes to help assist with and compliment the narrative. Although animators frequently acknowledge relationships between dance and animation, scarcely any scholarly work considers how animated film principles are used and applied within live dance performances. Additionally, although many scholars discuss the relationship between live dance and music and similarly animation and music, rarely has the collision of all three been scrutinized. In this article, I draw upon principles from animation film and choreomusical scholarship to show a complex relationship between the real and the pretend in a solo street dance performance. Based on detailed movement analysis of a short solo dance performance by Isaac "Turbo" Baptiste, I discuss the ways that moving image can influence live dancing bodies and create endless possibilities for choreomusical play.